XPC gene mutations in families with xeroderma pigmentosum from Pakistan; prevalent founder effect. (15th April 2018) - Ijaz, Ambreen; Basit, Sulman; Gul, Ajab; Batool, Lilas; Hussain, Abrar; Afzal, Sibtain; Ramzan, Khushnooda; Ahmad, Jamil; Wali, Abdul
ABSTRACT: Xeroderma pigmentosum (XP) is a rare autosomal recessive skin disorder characterized by hyperpigmentation, premature skin aging, ocular and cutaneous photosensitivity, and increased risk of skin carcinoma. We investigated seven consanguineous XP families with nine patients from Pakistan. All the Patients exhibited typical clinical symptoms of XP since first year of life. Whole genome SNP genotyping identified a 14 Mb autozygous region segregating with the disease phenotype on chromosome 3p25.1. DNA sequencing of XPC gene revealed a founder homozygous splice site mutation (c.2251‐1G>C) in patients from six families (A–F) and a homozygous nonsense mutation (c.1399C>T; p.Gln467*) in patients of family G. This is the first report of XPC mutations, underlying XP phenotype, in Pakistani population.